A Phenomenology Of The Therapeutic After Husserl And Merleau-Ponty (Existential Analysis: Journal of the Society for Existential Analysis, 2019)
This paper presents a phenomenology of the therapeutic emerging from interviews with ten mental health nurses. The phenomenology shows an irreducible tension between the 'I' and the 'not I', and the crucial difference between given and sensual meaning, linked to truthfulness. Phenomenology reveals method in research involving meaning as being a narrowing of language and thought.
Keywords: Phenomenology; meaning; language; method; sensual; therapeutic